Bidirectional associations between emotions and school adjustment. Issue 5 (10th January 2018) - Hernández, Maciel M.; Eisenberg, Nancy; Valiente, Carlos; Spinrad, Tracy L.; Berger, Rebecca H.; VanSchyndel, Sarah K.; Silva, Kassondra M.; Diaz, Anjolii; Thompson, Marilyn S.; Gal, Diana E.; Southworth, Jody
Abstract: Objective: We examined the relations of children's ( N  = 301) observed expression of negative and positive emotion in classes or nonclassroom school contexts (i.e., lunch and recess) to school adjustment from kindergarten to first grade. Method: Naturalistic observations of children's emotional expressivity were collected, as were teachers' reports of children's school engagement and relationship quality with teachers and peers. Results: In longitudinal panel models, greater teacher–student conflict and lower student engagement in kindergarten predicted greater negative expressivity in both school contexts. School engagement and peer acceptance in kindergarten positively predicted first grade positive emotion in the classroom. Suggestive of possible bidirectional relations, there was also small unique prediction (near significant) from negative expressivity at lunch and recess to higher teacher–student conflict, from negative expressivity in the classroom to low peer acceptance, and from positive expressivity in the classroom to higher peer acceptance. Conclusions: The pattern of findings suggests that the quality of experience at school uniquely predicts children's emotional expressivity at school more consistently than vice versa—a finding that highlights the important role of school context in young children's emotionality at school.